Plant growth stimulants and the effect of foliar feeding on the yield of some vegetable crops - Alimova R.А.,; Sagdiev М.Т. (Genius Journals, 2022)
When the light chestnut soil of the Tashkent region was studied, a positive effect of the application of growth-stimulating preparations in the cultivation of vegetable crops was established against the background of N120P60K60 for table beet and N180P60K60 for onion. On average, over two years of study (2019 - 2020), the increase in the yield of onion ranged from 8,5 to 48,7 t/ha compared to the control variant, while in table beet from 8,1 to 29,9 t/ha. The highest effect on yield for all varieties and hybrids of onion was achieved when N180P60K60 + gibberellin was used, as for table beet N120P60K60 + GA-3 gibberellin was used. The complex use of plant growth stimulants at the phase of various levels of mineral nutrition led to the reduction in the concentration of nitrates in onions and root crops of grown products. Foliar treatments by vegetation phases led to a significant accumulation of the mass fraction of sugar and vitamin C.
Keywords: cultivation of vegetable crops; growth stimulating preparations; foliar feeding; gibberellin GA-3